Optimal instructions to maximize attack efficiency in beginners and experienced fencers - Milic, M.; Janicijevic, D.; Nedeljkovic, A.; Cuk, I.; Mudric, M.; García-Ramos, A. (Motor control, 2021)
This study aimed to determine the instruction that maximizes fencing attack performance and to explore the sensitivity of a novel efficiency index (EI) that considers reaction time, attack velocity, and absolute error to discriminate between beginners and experienced fencers. Instructions that directed attentional focus internally (react as fast as possible and perform the attack movement as fast as possible) or externally (be as accurate as possible) were provided prior to stimulus presentation. The EI did not differ between the instructions in any group (p > .05), the instructions "react as fast as possible" and "be as accurate as possible" promoted in beginners the highest and the lowest EI, and the EI was higher for fencers. Our findings suggest that the EI could be recommended as a general index of fencing attack efficiency.